A cone beam computed tomography study based on three-dimensional cephalometric analysis of relationships between the lip-line and jaw deformity. (September 2022) - Teng, Caitian; Zhu, Junwei; Wang, Huifang; Yu, Qing
Abstract: Objective: The aim of this study was to use the cone beam computed tomography (CBCT) to study the relationships between the lip-line and mandible deformity. Design: CBCT data of 20 patients with jaw deformity (experimental group) and 20 patients without mandible deformity (control group) were selected. Use three-dimensional cephalometry to measure the reconstructed images of CBCT data simulated by the Materialise Interactive Medical Image Control System (Mimics), mark the related points, lines and planes of the three-dimensional craniomaxillofacial structure, and measure relevant distances and angles. The T-test, Pearson correlation analysis and Linear regression were used to analyze the characteristics of the lip-line and jaw deformity. Results: There was a significant difference in the lip-line between mandible deformity group and control group. Significant positive correlations could been found among the lip-line cant, the occlusal plane cant, the mandibular plane cant and the degree of mandible deformity (r=0.964, 0.942, 0.611, P < 0.01). A linear relationship was found between the left lip-line cant Y and the menton deviation X [the mandible deflection to the right was defined as positive, and the left lip-line below frankfort horizontal was viewed as positive] as Y= 0.340 + 0.505X. Conclusions: The lip-line of patients with jaw deformity was inclined, and the lip-line cant was positively correlated with the degree of mandible deformity, and there was a certain linear relationship between the two, which could provide a theoretical reference for clinicians to diagnose and treat patients with mandible deformity. Highlights: We analysed relationships between the lip-line and jaw deformities. We used 3D cephalometric analysis of the lip-line and mandible deformity. There was a relatively consistent trend of the lip-line and occlusal plane cants. There was a linear relationship between the lip-line cant and mandible deviation.